The Success of Cataract Surgery and the Preoperative Measurement of Retinal Function by Electrophysiological Techniques - Jing An; Lei Zhang; Yusheng Wang; Zuoming Zhang (Journal of Ophthalmology)
Purpose. To study the effect of different electrophysiological methods to evaluate retinal function prior to cataract surgery. Methods. Cataract patients who had no significant other eye disease were chosen. VA, pattern visual evoked potential (PVEP), electroretinogram (ERG), and multifocal electroretinogram (mfERG) responses were measured from 150 cataract patients and 20 control subjects. Results. When the preoperative VA was more than 0.3 in cataract patients, the amplitude of PVEP was not significantly different between cataract and control subjects. The amplitude of central point mfERG was significantly lower in cataract patients compared with control group from HM to 0.8 of preoperative VA. The 95% confidence intervals (CIs) of the amplitudes of center point mfERG were calculated for a range of preoperative VA values. Most of the patients within 95% CI of the center point mfERG had a postoperative VA more than 0.5. Conclusions. The amplitude of central point mfERG in cataract patients was the most relevant parameter to the preoperative VA compared with PVEP and ERG. The 95% CI of the amplitude of central point mfERG for each level of VA could help to evaluate preoperative macular function which is used to predict the outcome of cataract surgery.